The Effect of Gender Perception and Lifestyle on Purchase Decisions of NAYME.IDN Consumers - Dewi, Melati Kusuma; Kurnia, Dede; Yusup, Ismail (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The fashion industry is strongly influenced by lifestyle trends and changing consumer identity, especially among Generation Z. NAYME.IDN experienced fluctuating sales from October 2024 to September 2025 and an increase in male consumers, although the brand was initially positioned for female consumers. This study aims to describe gender perception, lifestyle, and purchase decisions, and to analyze the effect of gender perception and lifestyle on purchase decisions for NAYME.IDN products. This study used a quantitative method with a descriptive-verificative approach. Data were collected through a structured questionnaire using a five-point Likert scale. The sample consisted of 35 Generation Z consumers who had purchased NAYME.IDN products through online or offline channels. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination, t-test, and F-test. The results show that gender perception, lifestyle, and purchase decision are in the high category. Gender perception has no significant partial effect on purchase decision, while lifestyle has a positive and significant effect. Simultaneously, gender perception and lifestyle significantly affect purchase decision, with an R² value of 0.502. These findings indicate that lifestyle is a more dominant factor in shaping purchase decisions for NAYME.IDN products.